Public perception of population health risks in Canada: health hazards and health outcomes. (23rd March 2009) - Krewski, Daniel; Lemyre, Louise; Turner, Michelle C.; Lee, Jennifer E.C.; Dallaire, Christine; Bouchard, Louise; Brand, Kevin; Mercier, Pierre
The focus of this article is a descriptive account of the perceptions of five health hazards (motor vehicles, climate change, recreational physical activity, cellular phones, and terrorism) and five health outcomes (cancer, long-term disabilities, asthma, heart disease, and depression) from a recent survey of 1503 Canadians. In an attempt to shed light on factors that influence risk perception in Canada, the extent to which these exemplars are perceived as high in risk and controllability, as well as the extent to which knowledge and uncertainty surrounding them is high, was examined. The degree to which these exemplars are deemed acceptable and generate worry among Canadians was also examined. Variation was observed in the extent to which different health hazards and outcomes are perceived on the various dimensions. Perceptions of health hazards and outcomes also vary significantly by gender, age, and education. Findings are compared to existing research on risk perception.